DAKWAH EKONOMI DALAM KITAB KUNING Konsepsi Syaikh Muhammad Nawawi Mengenai Manajemen Distribusi Zakat - Syamsul Yakin (Faculty of Dakwah and Communication, UIN Syarif Hidayatullah Jakarta, 2022)
The kitab kuning (pre-modern book) has been primary references of islamic studies in Indonesia. The kitab kuning content covers a variety of topics such as zakat. Zakat is the third pillar of Islam. Unlike the other pillars of Islam, zakat has both personal and social dimensions. This study aims to describe and find the relevance of the zakat concepts in kitab kuning to the modern concepts about management of zakat distribution. The research studied Syaikh Muhammad Nawawi’s conception on management of zakat distribution in his fikih works such as Kaasyifah al-Sajaa and Tafsir Munir. The study used descriptive qualitative methods to provide an overview of the kitab kuning conception on management of zakat distribution. The result of this study showed that the management of zakat distribution in kitab kuning conceptions are still conventional. While some concepts contain ideas that are relevant to the context modern management of zakat distribution.